2018
DOI: 10.1590/0004-282x20180114
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in Parkinson's disease and increased cardiovascular risk

Abstract: Restless legs syndrome (RLS) is a disorder commonly found in patients with Parkinson's disease, with descriptions for both conditions impairing dopaminergic transmission in central nervous system. Previous studies in varied populations indicate an association between the presence of RLS and increased cardiovascular risk and, so far, there are no consistent studies of this association in Parkinson's disease. Objective: To analyze the influence of RLS on cardiovascular risk in patients with Parkinson's disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous studies 37,38 have shown that more and more PD patients are complicated by hypertension, diabetes, hyperhomocysteine, dyslipidaemia, smoking and other risk factors for cerebrovascular diseases, suggesting that cognitive impairment in PD patients may be related with those risk factors. Cramer et al 39 conducted a 5‐year follow‐up study of 1674 non‐PD participants, and have found that statin lipid‐lowering drugs can reduce the incidence of cognitive dysfunction by about 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 37,38 have shown that more and more PD patients are complicated by hypertension, diabetes, hyperhomocysteine, dyslipidaemia, smoking and other risk factors for cerebrovascular diseases, suggesting that cognitive impairment in PD patients may be related with those risk factors. Cramer et al 39 conducted a 5‐year follow‐up study of 1674 non‐PD participants, and have found that statin lipid‐lowering drugs can reduce the incidence of cognitive dysfunction by about 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a circadian profile of dopamine levels, in addition to dopaminomimetic drugs, may contribute to the coexistence of RLS and nocturnal compulsive behaviors in PD Figure1. ICD-RBs type and frequency patients (19,20). Lastly, in later stages of PD, a dopamine deficiency may occur in the nigro-striatal pathway, causing hypersensitivity of D1 and D2 receptors primarily located in the dorsal striatum, and dopaminergic medications may lead to desensitization of dopamine receptors (21).…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in dopaminergic transmission, common in the etiology of PD and RLS, may explain why the prevalence of RLS in patients with PD is high. 21 Dysfunction of dopaminergic signaling can directly change the brain network. Hence, we did fMRI analysis to investigate the altered patterns of brain activity and functional connections in PD patients with and without RLS by combining both ReHo and seed-based FC analyses.…”
Section: Discussionmentioning
confidence: 99%